Skilled emigration, business networks and foreign direct investment - Maurice Kugler; Hillel Rapoport (Center for Economic Studies and ifo Institute (CESifo), 2005)
In a global context foreign direct investment (FDI) and migration substitute one another in the matching process between workers and firms. However, as labor flows can lead to the formation of business networks, migration can actually facilitate FDI in the long-run. We first present a stylized model for a small open economy illustrating these offsetting effects. We then use U.S. data on bilateral labor inflows and capital outflows to measure the extent of contemporaneous substitutability and dynamic complementarity between migration and FDI. We find that brain drain and FDI inflows are negatively correlated contemporaneously but that skilled migration is associated with future increases in FDI inflows. We also find suggestive evidence of substitutability between current migration and FDI for migrants with secondary education, and of complementarity between past migration and FDI for unskilled migrants.
Keywords: O41; F43; F22; 330; brain drain; foreign direct investment inflows; migrant ties and business networks; Brain Drain; Direktinvestition; Business Network; Vereinigte Staaten